Progesterone receptor expression in the developing mesocortical dopamine pathway: importance for complex cognitive behavior in adulthood - Willing, Jari (Neuroendocrinology, 2015)
BACKGROUND: Numerous psychiatric and behavioral disorders such as Autism, Attention Deficit Disorder and Schizophrenia may involve disruptions in the development of the mesocortical dopamine pathway, consisting of dopaminergic projections from the midbrain ventral tegmental area (VTA) to the medial prefrontal cortex (mPFC). Nuclear steroid hormone receptors are powerful transcription factors and can profoundly and permanently alter fundamental processes of neural development. Nuclear progesterone receptor (PR) is transiently expressed in both the VTA and the PFC of rodents during perinatal life, suggesting that PR may regulate the normal development of this important behavioral circuit. METHODS AND RESULTS: Here, we demonstrate that virtually all PR immunoreactive (PRir) cells in the VTA also express tyrosine hydroxylase-ir (THir). In addition, retrograde tract tracing reveals that many PRir cells in the VTA project to the mPFC. Administration of a PR antagonist to rats during the neonatal period decreased THir fiber density in prelimbic mPFC of juveniles (P25) and decreased levels of THir in the VTA of adults. Neonatal treatment with a PR antagonist impaired adult performance on a passive inhibitory avoidance task and an attentional set shift task, measures of behavioral inhibition/impulsivity and cognitive flexibility, respectively. THir levels in VTA were reduced and cognitive flexibility was impaired in PR knockout mice as well. CONCLUSIONS: These findings provide novel insights into a potential role for PR in the developmental etiology of behavioral disorders that involve impairments in complex cognitive behaviors and have implications for the use of synthetic progestins in humans during critical neurodevelopmental periods.